Hydroalcoholic Leaf Extract of Punica granatum, alone and in Combination with Calcium Hydroxide, Is Effective against Mono- and Polymicrobial Biofilms of Enterococcus faecalis and Candida albicans - Monica Naufel Sousa; Alessandra Teixeira Macedo; Gabriella Freitas Ferreira; Haryne Lizandrey Azevedo Furtado; Aruanã Joaquim Matheus Costa Rodrigues Pinheiro; Lídio Gonçalves Lima-Neto; Valéria Costa Fontes; Rayana Larissa Pinheiro Soares Ferreira; Cristina Andrade Monteiro; Angela Falcai; Lillian Nunes Gomes; Queila da Silva Rosa Bragança; et al. (Antibiotics, 2022)
Failures in endodontic treatments are mostly associated with the difficulty in eradicating microbes of the root canal system, highlighting the need to develop novel effective antimicrobials. Punica granatum (pomegranate) leaf hydroalcoholic extract may be a potential alternative in canal dressing, owing to its antimicrobial properties. The objective of this study was to evaluate the antimicrobial activity of hydroalcoholic leaf extract of Punica granatum (HEPg) alone or in combination with calcium hydroxide (Ca(OH)2) against Enterococcus faecalis and Candida albicans in isolation and in mono- and polymicrobial biofilms. Microdilution tests in broth and assays for inhibition of biofilm formation were carried out to evaluate the antimicrobial properties of HEPg and HEPg + Ca(OH)2 against Enterococcus faecalis and Candida albicans. The cytotoxicity of HEPg in HaCaT cells was evaluated by MTT assay. HEPg and HEPg + Ca(OH)2 exerted significant antimicrobial activity against planktonic cells and mono- and polymicrobial biofilms. The combination of Punica granatum extract with Ca(OH)2 appears to be a promising alternative in endodontic treatments, which could be tested in vivo to confirm the efficacy of this mixture in disinfecting root canal systems.